Kınık Höyük in South Cappadocia - d’Alfonso, Lorenzo (Altorientalische Forschungen, 2018)
This note complements the preliminary comparative stratigraphy of excavated sites of Cilicia published in AoF 44/2 with the new stratigraphic data obtained at the ongoing excavation of Niğde Kınık Höyük, in South Cappadocia. South Cappadocia lies directly north of Cilicia beyond the Taurus mountains, and from Prehistory it has controlled the access from Cilicia to the Anatolian Plateau. The region knew periods of minor, and more intense, participation in the cultural developments experienced in Cilicia, and the note is intended to provide basic stratigraphic information to start the study of this relation in a more precise and comprehensive way. The note only adds the information for the site of Kınık Höyük, but it is a strong invitation to other colleagues working in Cappadocia to build a similar comparative stratigraphy.